2021
DOI: 10.1086/711654
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of Educational System Consolidation: The Case of China’s Rural School Closure Initiative

Abstract: Global trends of fertility decline, population aging, and rural outmigration are creating pressures to consolidate school systems, with the rationale that economies of scale will enable higher quality education to be delivered in an efficient manner, despite longer travel distances for students. Yet, few studies have considered the implications of system consolidation for educational access and inequality, outside of the context of developed countries. We estimate the impact of educational infrastructure conso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…Given evidence that school closures are detrimental to educational performance, particularly for students of disadvantaged backgrounds 2,7,[15][16][17][18][19][20] , the large socio-economic, geographic, and demographic disparities in exposure to distance learning suggest that the COVID-19 pandemic is likely to exacerbate inequalities in learning outcomes across the U.S.…”
Section: This Study Introduces and Analyzes A Us School Closure And Dmentioning
confidence: 99%
“…Given evidence that school closures are detrimental to educational performance, particularly for students of disadvantaged backgrounds 2,7,[15][16][17][18][19][20] , the large socio-economic, geographic, and demographic disparities in exposure to distance learning suggest that the COVID-19 pandemic is likely to exacerbate inequalities in learning outcomes across the U.S.…”
Section: This Study Introduces and Analyzes A Us School Closure And Dmentioning
confidence: 99%
“…29 Controlling for provincial fixed effects, Hannum, Liu, and Wang (2021) find no statistically significant differences between closure and non-closure villages in terms of village per-capita income, local wage, fraction of workers in the labor force, the fraction of migrant workers, village per-capita spending overall and on education, and the implementation rate of health and insurance policies between closure and non-closure villages. The key statistically significant difference is that closure villages have on average 11 percent less households than non-closure villages.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies suggest that some poor rural families might be more likely to shoulder costs for boys than girls: research in China suggests that girls' educational attainment has been more susceptible than boys' to poverty (Cherng and Hannum 2013;Liu and Hannum 2017). Earlier research has also shown that rural girls are particularly affected by school consolidation, possibly because enrollment decisions for boys are more sensitive to quality, while those for girls are more sensitive to distance (Hannum, Liu, and Wang 2021).…”
Section: Impact Of School Consolidationmentioning
confidence: 99%
See 2 more Smart Citations